OCCUPATIONAL INFECTIOUS RISK IN DENTISTRY - AWARENESS AND PROTECTION. - Miglena Balcheva; Vladimir E. Panov; Christiana Madjova; Genoveva Balcheva (Peytchinski Publishing, 2015)
Introduction: The syllabi of many dental subjects include topics about infectious diseases. Students are informed about their symptoms, transmission routes, prevention and treatment. Great attention is paid also on the necessity of full medical history, appropriate disinfection and sterilization protocols and the use of personal protective means. Purpose: We aim to determine to what extent dental students and dentists evaluate the risk of infectious diseases and protect themselves and their patients. Participants and methods: Dental students in their fourth, fifth and sixth year, and dentists fill an anonymous questionnaire about the protection means they apply - types and frequency of usage. They are asked if they are vaccinated against HBV and if they are informed about their patients' infections, as well. Results: 94 dental students and dentists from Varna have filled the questionnaire. All of them use different protection means in their everyday clinical practice and most of them are HBV vaccinated. Conclusions: It is absolutely necessary to protect ourselves and the health of our patients. The adequate academic training of dental students implies future responsible work.